Profil Disolusi Parasetamol Mukoadhesif Menggunakan Kombinasi Polimer Hydroxy Propyl Metyl Celluloce (HPMC) dan Natrium Alginat - Maria Dona Octavia; Novi Rini Novita; Auzal Halim (Jurnal Farmasi Higea, 2010)
Research on the dissolution profile of paracetamol by using a combination of polymer mucoadhesive hydroxypropyl methylcelulloce (HPMC) and sodium alginate has been done. This study aimed to see the effect of the combination of polymer HPMC and Sodium Alginate on the dissolution profile of paracetamol mucoadhesive. in this study were made four formula granule containing 100 grams of acetaminophen as an active ingredient and combination of HPMC with sodium alginate with various concentrations: 50 grams of sodium alginate (F1), 40 grams of sodium alginate and 10 grams of HPMC (F2), 30 grams of sodium alginate and 20 grams of HPMC (F3) and 50 grams of HPMC (F4), where Avicel PH 102 is used as a filler. The resulting granules are evaluated which include : content level,  dissolution profile and test bioadhesif granules. Dissolution profiles performed by the method of rowing in the  900 mL medium of pH 5.8 buffer fosphat, 37±0.5°C and a speed of 50 rotation/min. The measurement results at minute 60 shows that the average granule dissolution F1, F2, F3 and F4 are 8.8341%, 9.2838%, 12.9828% and 17.2589% respectively. The Conclusion is the combination of paracetamol mucoadhesive polymers HPMC with sodium alginate showed an influence on the dissolution profile of paracetamol, where F1 formula shows the best dissolution profiles among the other four formulas.